Improved meet‐in‐the‐middle attacks on reduced‐round Joltik‐BC. (17th March 2021) - Li, Manman; Chen, Shaozhen
Abstract: Joltik‐BC is an internal tweakable block cipher of the authenticated encryption algorithm Joltik, which was a second‐round finalist in the CAESAR competition. The authors study the key‐recovery attacks on Joltik‐BC under meet‐in‐the‐middle attack. Utilising the subtweakey difference cancellation, the freedom of the tweak and the differential enumeration, they attack on nine‐round Joltik‐BC‐64‐64 by constructing a precise six‐round meet‐in‐the‐middle distinguisher with 2 53 plaintext–tweak combinations, 2 52.91 Joltik‐BC blocks and 2 54.1 nine‐round Joltik‐BC‐64‐64 encryptions. Moreover, they attempt to attack on 11‐round Joltik‐BC‐128‐64 for the first time by constructing a seven‐round meet‐in‐the‐middle distinguisher with 2 53 plaintext–tweak combinations, 2 114 Joltik‐BC blocks and 2 123 11‐round Joltik‐BC‐128‐64 encryptions.